2020
DOI: 10.21203/rs.3.rs-24853/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sharing genomic data from clinical testing with researchers: public survey of expectations of clinical genomic data management in Queensland, Australia.

Abstract: Background: There has been considerable investment and strategic planning to introduce genomic testing into Australia’s public health system. As more patients’ genomic data is being held by the public health system, there will be increased requests from researchers to access this data. It is important that public policy reflects public expectations for how genomic data that is generated from clinical tests is used. To inform public policy and discussions around genomic data sharing, we sought public opinions o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…They expressed the least trust in pharmaceutical companies, global for-profit companies and health insurance companies. Other studies assessing public opinions globally26 and in the UK, USA, Australia, Canada and Singapore2 27–32 confirm that individuals distinguish between research conducted by public and private actors. Our study identified a further distinction regarding for-profit companies: strong trust in Swiss for-profit companies increased willingness to participate in personalised health research, whereas trust in international for-profit companies had no influence.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…They expressed the least trust in pharmaceutical companies, global for-profit companies and health insurance companies. Other studies assessing public opinions globally26 and in the UK, USA, Australia, Canada and Singapore2 27–32 confirm that individuals distinguish between research conducted by public and private actors. Our study identified a further distinction regarding for-profit companies: strong trust in Swiss for-profit companies increased willingness to participate in personalised health research, whereas trust in international for-profit companies had no influence.…”
Section: Discussionmentioning
confidence: 84%
“…Large amounts of health data and samples are necessary to achieve the goals of personalised medicine, requiring that individuals participate in biomedical research by donating their health data and samples, and that the samples and data be available for reuse in future research studies 1. Studies have shown that public preferences around sharing personal health and genetic information in a research setting vary depending on societal, demographic and jurisdictional context 2. In Switzerland, we previously found that the public generally holds a positive opinion towards personalised health research, and that a majority are hypothetically willing to donate data and samples for such projects 3.…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen Capability projects were commissioned within the Strategy and Legacy Rounds (Table 2). Projects focused on (1) preparation of the health system for genomics, or (2) support or evaluation of Clinical projects [27][28][29][30][31][32][33][34][35] . In addition, seven projects designed by the CAG were funded in the Strategy and Legacy Rounds (Table 2) that focused on areas of need for the patient community and patient support mechanisms within the health system 36 .…”
Section: -2021mentioning
confidence: 99%
“…With the growing integration of genomics into clinical AQ1 AQ2 AQ3 AQ4 AQ5 medicine [ 1 ], the scale, scope and complexity of genomic research is inevitably increasing [ 2 ]. There are many ethical considerations associated with genomic research, including the nature of consent [ 3,4,5,6 ], procedures around the disclosure/non-disclosure of results [ 7,8,9,10,11 ], sample ownership and data storage/sharing [ 12,13,14,15 ], the shared nature of genetic information [ 16 ], and genetic discrimination with insurance policies [ 17,18,19 ]. Genomic research, therefore, requires robust ethical review.…”
Section: Introductionmentioning
confidence: 99%